2016
DOI: 10.1016/j.rgg.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Classification of rocks of the Bazhenov Formation

Abstract: In this study, we propose a new classification of rocks of the Bazhenov Formation based on the proportions of four principal components (siliceous, clay, and carbonate minerals and organic matter (kerogen)) of mostly biochemogenic and, to a lesser extent, allothigenic origin. The classification is based on the results of mineralogical and chemical analyses of more than 400 core samples from 15 wells drilled within the Bazhenov Formation, West Siberian petroleum basin. Four major classes of rocks, divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 5 publications
0
7
0
5
Order By: Relevance
“…Our experiments showed that strain BYF could grow with barite or celestine. The barite occurrence in the Bazhenov Formation rocks has been documented [45]. The barium concentration in the 1-R water is not sufficiently high to speculate that barite fuels sulfate reduction in the aquifer.…”
Section: Strain Byf Morphology and Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Our experiments showed that strain BYF could grow with barite or celestine. The barite occurrence in the Bazhenov Formation rocks has been documented [45]. The barium concentration in the 1-R water is not sufficiently high to speculate that barite fuels sulfate reduction in the aquifer.…”
Section: Strain Byf Morphology and Physiologymentioning
confidence: 99%
“…High strontium content up to 500 mg/L is a wellknown characteristic of the West Siberian Megabasin [46]. It is also conceivable that concentration of sulfate could be higher in pore water of the rock matrix due to oxidation of such minerals as pyrite, the high content of which is recorded in the Bazhenov Formation [45]. Sulfate may also remain undetected in the relict marine water localized in spatially isolated sulfate-rich parts of the aquifer system.…”
Section: Strain Byf Morphology and Physiologymentioning
confidence: 99%
“…Ryzhkova (A.A. Trofimuk Institute of Petroleum Geology and Geophysics, Novosibirsk). The section was described using the classification and names of the Bazhenov Formation rocks adopted at the IPGG SB RAS (Kontorovich et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Based on results of the analyses, the chemical composition of rocks was recalculated to the mineral one, using the MINLITH software proposed by Rosen et al (2000). Based on the recalculation data, each sample was given a lithological name according to the adopted classification by Kontorovich et al (2016) (in Russian) and Lazar et al (2015) (in English). Following these authors, the rocks with >50% biogenic quartz were called siliceous mudstones, and those with <50% clay material and <50% biogenic quartz, siliceous-argillaceous mudstones.…”
Section: Methodsmentioning
confidence: 99%